Antibacterial activity and GC-MS analysis of the Citrus amblycarpa (Hassk) Ochse essential oil - Sri Mulyani (Indonesian Journal of Pharmacy, 2009)
A research about anti-bacterial activity and components of essential oil from leaves and peels of Citrus amblycarpa have been done.The components of essential oil had been identified by using GC-MS and anti-bacterial activity against S. aureus ATCC 25923 and E. coli ATCC 25922 had been determined with liquid dilution method. The component of essential oilfrom leaves that can be identified are β-pinene, linalool, citronellal, citronellol and geraniol, while from peels are β-pinena, cymene, limonene and citronellal.Oil from the leaves has stronger anti-bacterial activity against S. aureus than from peels. On the other hand oil from peels is stronger anti-bacterial activity against E coli.Key words : Citrus amblycarpa, essential oil, anti-bacterial activity.